Les sols de jardins, supports d’une agriculture urbaine intensive - Christophe Schwartz (VertigO)
Vegetable gardens are localised in human impacted environments, at the interface between agriculture, city and industry. Therefore, garden soils are highly fertile and show very contrasted characteristics resulting from various gardening practices. These practices are influenced by different ecological and economical objectives of the gardeners. At the same time, garden soils are probably the less studied of all the soils dedicated to food production. One of the few surveys on French garden soils was conducted in the Lorraine region. These soils present an upper cultivated horizon of 20 to 40 cm depth and of dark color. Their organic matter content is meanly over 4% compared to agricultural soils (1 to 3%). Seventy percent of the garden soils show very high concentrations of nutrients. Mean total heavy metal concentrations in garden soils are twice higher than in agricultural soils. This contamination is correlated in a growing range, with the distance to atmospheric pollutants emissions, the geochemical background, the mainly intensive gardening practices and the age of the garden. Out of the results obtained from targeted regions, additional work is necessary at the (inter)national scale (i) to propose a typology of garden soils and (ii) to obtain representative databases for future risk assessments.garden, urban, soil, vegetation, Technosols, Anthrosols, quality